1997
DOI: 10.1093/bja/78.5.576
|View full text |Cite
|
Sign up to set email alerts
|

Increased intraperitoneal pressure up to 15 mm Hg does not reliably induce haemodynamic changes in pigs

Abstract: Haemodynamic alterations occur consistently with laparoscopic surgery in humans. These haemodynamic changes have never been reproduced in an animal model without additional potentiating factors. As these alterations may be deleterious in some patients and as the cause is only partly understood, we have used an animal model to study these changes. Pneumoperitoneum with intraperitoneal pressures of up to 15 mm Hg were produced in pigs, in the same way as for laparoscopic surgery in humans. Arterial pressure, car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…By contrast, increases in systemic vascular resistances are less constant and less marked in the pig‐model than in human studies. We observed no significant change in our study, in accordance with the results of Lentschener and colleagues (7), and Ho and colleagues only observed a limited 18% rise in systemic vascular resistances (14). Although it is possible that our study was underpowered to show a moderate increase in systemic vascular resistance, it nevertheless confirms that only slight variations in systemic vascular resistance can be observed when the pig‐model is used to study laparoscopy.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…By contrast, increases in systemic vascular resistances are less constant and less marked in the pig‐model than in human studies. We observed no significant change in our study, in accordance with the results of Lentschener and colleagues (7), and Ho and colleagues only observed a limited 18% rise in systemic vascular resistances (14). Although it is possible that our study was underpowered to show a moderate increase in systemic vascular resistance, it nevertheless confirms that only slight variations in systemic vascular resistance can be observed when the pig‐model is used to study laparoscopy.…”
Section: Discussionsupporting
confidence: 93%
“…However, haemodynamic studies have led to conflicting results. Some authors found no significant changes, while others found a decrease in CO associated with a rise in SVR (7, 8). It was claimed that experimental conditions can considerably influence the results, and validity of the pig‐model has been debated (7, 8).…”
mentioning
confidence: 98%
“…This discrepancy between human and pigs is in accordance with other reports (25,26). The reduction of flow in the femoral vein was much greater than in the portal vein.…”
Section: Discussionsupporting
confidence: 92%
“…Another possible explanation is that 12 mmHg of CO 2 PP does not affect young pigs in the same way as it does humans. Lentschner et al [13] failed to show any effect of up to 15 mmHg of CO 2 PP in MAP, CO, PAP, or systemic arterial resistance in pigs, and they concluded that PPinduced hemodynamic changes are dependent on species. Others, who have studied piglets, such as Graham et al [4], have found alterations in at least some of these parameters, so species differences cannot be the only factor.…”
Section: Discussionmentioning
confidence: 99%